The Netherlands as a winter refuge for Light-bellied Brent Geese Branta bernicla hrota - Koffijberg, Kees; van Winden, Erik; Clausen, Preben (Wildfowl, 2013)
From 1978/79 onwards, eleven influxes of East Atlantic Light-bellied Brent Geese Branta bernicla hrota were recorded in the Netherlands, to the south of their regular wintering areas in northern Denmark and northeast England. During most influxes, c. 3–6% of the total population occurred in the Netherlands, but large influxes in 1995/96 and 2010/11 involved as many as 800–907 individuals, i.e. 18% and 11% of the flyway population respectively. Core wintering sites within the Netherlands were in the southwest Wadden Sea, in the northern part of Noord-Holland and in the Delta area in the southwest of the country. The first two of these areas are thought to have been more regular wintering areas for Light-bellied Brent Geese in the first part of the 20th century, although good documentation on numbers is lacking. The highest number recorded at a single site was 245 birds in Polder Kimswerd/Eendracht, Friesland, in December 2010. The distribution pattern was similar during all influxes, indicating traditional site use by the wintering flocks. Winters with peak numbers in the Netherlands show a significant, negative correlation with average daily temperatures at the Danish wintering sites. During prolonged and/or heavy cold spells, feeding conditions in Denmark deteriorate due to ice- or snow cover, making both aquatic and agricultural food resources unavailable and forcing birds to depart; this was confirmed by count data from Denmark. In 1995/96, phenological patterns and sightings of marked birds also indicated an influx from birds from the wintering site at Lindisfarne in the UK, but this could not be confirmed for more recent winters. Sightings of marked birds showed that at least some birds (eight out of 34 observed individuals) were involved in successive influxes; in non-influx years they were seen regularly at wintering sites further up the flyway as well as on breeding sites at Svalbard. The regular patterns of influxes, the traditional use of particular sites during influx years and repeated observations of the same individuals at these sites (which may transfer knowledge of alternative wintering sites in the Netherlands to their offspring, indicated by ringed birds being seen with their goslings) illustrates that the Netherlands should be considered as a regular hard weather winter refuge for the sub-species. Appropriate measures therefore should be taken to include these sites within the national Natura 2000 network.